Effectiveness and safety of once-weekly semaglutide for weight loss in adults with overweight or obesity: a systematic review of randomized controlled trials - Singha, Snehashis; Majumder, Rajasree (International Journal of Basic & Clinical Pharmacology, 2026)
Obesity is a major global health problem associated with diabetes, cardiovascular disease, and premature mortality, and lifestyle modification alone often results in insufficient long-term weight reduction. Semaglutide, a once-weekly glucagon-like peptide-1 receptor agonist, has demonstrated significant weight-loss effects in randomized trials; however, a consolidated evaluation of its efficacy, safety, dose–response relationship, and metabolic effects across adult populations is required. We conducted a systematic review of randomized controlled trials identified through a comprehensive search of seven databases and trial registries (PubMed, Embase, Cochrane CENTRAL, Scopus, Web of Science, ClinicalTrials.gov, and WHO ICTRP) from January 2000 to January 2025. Of 923 records screened, 41 trials met eligibility criteria and 36 contributed quantitative data, enrolling adults with body mass index ≥30 kg/m² or ≥27 kg/m² with comorbidities and evaluating once-weekly subcutaneous semaglutide (0.5 mg, 1.0 mg, or 2.4 mg) for at least 12 weeks versus placebo or active comparators. Risk of bias was assessed using the Cochrane RoB 2 tool, and random-effects models were used to generate pooled estimates. Among 23,184 participants, semaglutide resulted in a mean weight reduction of -11.82% (95% CI -13.06 to -10.53), with the greatest effect observed at the 2.4 mg dose (-14.89%, 95% CI -16.41 to -13.21), and significantly increased the likelihood of achieving clinically relevant weight-loss thresholds (p<0.0001 for all efficacy outcomes). Significant improvements were also observed in glycaemic and cardiometabolic parameters, including reductions in HbA1c (-0.89%), fasting glucose (-14.7 mg/dL), triglycerides (-22.8 mg/dL), and systolic blood pressure (-5.81 mmHg). Gastrointestinal adverse events were more frequent with semaglutide but were generally mild to moderate, and the incidence of serious adverse events (SAEs) was comparable to control groups. Overall, once-weekly semaglutide produces substantial and sustained weight loss with meaningful metabolic benefits and an acceptable safety profile, supporting its role as an effective pharmacological option for the management of obesity.